Experimental study on the electrokinetic migration process of Hangzhou sludge. Issue 10 (1st July 2020) - Tao, Yanli; Zhou, Jian; Gong, Xiaonan; Luo, Zhanyou
Abstract: The migration of cations, which leads to the transportation of water molecules, is the essential driving force of electrokinetic dewatering. Several bench-scale experiments on Hangzhou sludge were performed using ferrum, graphite, copper, and aluminum electrodes. The element contents of Na, K, Mg, Ca, Fe, Al, and Cu in the effluent water as well as in the treated soil were measured to investigate the migration process of the corresponding cations. The electrokinetic drainage was noted to have a higher total content of the considered elements compared to that in gravity drainage, which demonstrated that electrokinetic treatment is effective for bound water. In the electrokinetic drainage, the contents of Na and K were much higher than those of other elements. Furthermore, the steady contents of Na and K in the electrokinetic drainage demonstrated the consistent electrokinetic mobility of Na and K ions. Ca and Mg ions tended to precipitate in the cathodic area. Most of the Fe ions generated from the reaction at the anode remained in the anodic area. The extremely low Cu content in the drainage and soil meant that no variations could be observed. Different cations were noted to have different electrokinetic mobilities. Higher electrokinetic mobilities were observed for cations having lower valency or smaller atomic weights. The order of ion electrokinetic mobility was noted to be Na + > K + > Mg 2+ > Ca 2+ > Al 3+ > Cu 2+ > Fe 2+ /Fe 3+ . Therefore, electrokinetic dewatering depends primarily on the presence of cations having a low valency or small atomic weight such as Na, K, Ca, Mg, and Al ions. Fe and Cu ions have low electrokinetic mobility and do not contribute considerably to the transportation of water molecules. The study provided guidance in the application evaluation of the electrokinetic technique in drying various soils.